ERGO-SMART CONSTRUCTION AND SUSTAINABLE PROJECT MANAGEMENT FOR OPTIMIZING TEMPORARY HOUSING DESIGN POST-EARTHQUAKE IN PASAMAN BARAT REGENCY - Barkhia Yunas; Mutia Alius; Ranti Mustika Putri (PT. Radja Intercontinental Publishing, 2026)
This study presents an integrated approach to optimizing post-earthquake temporary housing (Huntara) design in Pasaman Barat Regency, West Sumatra, Indonesia, through the application of Ergo-Smart Construction and Sustainable Project Management principles. Following the 2022 earthquake that damaged over 1,100 buildings, the urgent need for efficient, comfortable, and structurally sound temporary shelters became evident. This research employed a mixed-method approach combining field surveys, ergonomic analysis, structural modeling using ETABS software, and sustainable project management strategies. The study developed a 36 m² single-story temporary housing model featuring brick masonry walls reinforced with ferrocement overlay, practical columns, and ring beams designed to resist seismic loads in accordance with SNI 1726:2019. Structural analysis revealed that all stress components remained well below material capacity, with safety factors ranging from 2.68 to 13.7. Ergonomic evaluation confirmed compliance with international standards for spatial dimensions, ventilation, lighting, and accessibility. The modular design utilizing ferrocement overlay demonstrated a 25% acceleration in construction time while maintaining structural integrity. This research contributes a replicable, evidence-based shelter design framework integrating structural safety, occupant comfort, and construction efficiency for disaster-prone regions.